Abstract 15499: The Increase of Proplatelets and Tpo in Circulation May be a New Pathological Mechanism of Thrombosis - Yang, Mo; Li, Liang; zhang, hua; zeng, kuan; Yang, Yanqi (Circulation (New York, N.Y.), 2020)
IntroductionPlatelets are produced from megakaryocytes, which mainly regulated by thrombopoietin (TPO) and 5-HT. We hypothesized that the secretion of inflammatory cytokines increased in patients with thrombosis under stress or inflammation, leading to increased TPO levels, which in turn increased production capacity of platelet, and increased the number of platelet intermediates proplatelets into the circulation. Therefore, the increase in the number of proplatelets in the circulation, and the increase in plasma TPO levels may be a new pathological mechanism of thrombosis. MethodsTPO was detected by ELISA. Proplatelets from patients were stained with CD41-FITC and further confirmed by a fluorescence microscope and flow cytometry. The in vitro proplatelets were tested by CD41-FITC staining under a fluorescence microscope and flow cytometry detection. ResultsOur clinical data demonstrated that patients' plasma TPO levels were significantly higher with acute inflammation state compared with healthy subjects (181.1 ± 35.38 vs 96.1 ± 9.7 pg/ml, p<0.001, n=65). The plasma TPO levels of cerebral infarction patients (186.2±12.5 pg/ml, n=20) were significantly higher than that of the control group (122.3±10.2 pg/ml, n=20). The number of platelets in patients with cerebral infarction (222.11±8.55 х109/L, n=20) was slightly higher than that in the control group (206.55±8.83 х109/L, n=20). More large platelets or proplatelets were found in the circulating blood of patients with cerebral infarction, which was significantly different from the control group (n=8, p<0.05). In vitro study confirmed that in 200 megakaryocytes (MKs), more proplatelets were produced in the TPO group (100 ng/ml, 18±2.5%) and in the 5-HT group (100 nM, 15±3.2%), while the control group was only (7±3.2) % (n=5). The effects of TPO/ 5-HT were interfered with by its receptor blockers, confirming that their effects were mediated by its receptors. Both TPO and 5-HT affect the cytoskeleton by activating p-ERK1/2, reorganizing F-actin to generate proplatelets, and its role was blocked by PD98059. ConclusionsThe studies showed that the increase of proplatelets in circulation and TPO levels in plasma may be a new pathological mechanism of cerebral infarction or thrombosis.